2008
DOI: 10.1016/j.jcp.2008.07.019
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of explicit time integration schemes for use with the generalized interpolation material point method

Abstract: The stability and accuracy of the Generalized Interpolation Material Point (GIMP) Method is measured directly through carefully-formulated manufactured solutions over wide ranges of CFL numbers and mesh sizes. The manufactured solutions are described in detail. The accuracy and stability of several time integration schemes are compared via numerical experiments. The effect of various treatment of particle "size" are also considered. The hypothesis that GIMP is most accurate when particles remain contiguous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 15 publications
0
84
0
Order By: Relevance
“…Using the cpGIMP, Wallstedt and Guilkey [23] demonstrated that the USL scheme performs dramatically better than an alternative 'update stress first (USF)' scheme.…”
Section: Review Of the Mpm And Gimp Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the cpGIMP, Wallstedt and Guilkey [23] demonstrated that the USL scheme performs dramatically better than an alternative 'update stress first (USF)' scheme.…”
Section: Review Of the Mpm And Gimp Methodsmentioning
confidence: 99%
“…This allows verification of nonlinear codes or algorithms by running them with the computed external force and demonstrating that the assumed solution is recovered. Two examples constructed based on the MMS in this paper are similar to those that were constructed and described by Wallstedt and Guilkey [23] for studying the effects of different time integration schemes in the GIMP algorithm. The following error norm was adopted to investigate spatial convergence of these two examples: (27) in which N t and N p are total number of particles and time steps, respectively, u app (x p , t i ) and u exact (x p , t i ) are the calculated and analytical displacement vectors, respectively.…”
Section: Numerical Examplesmentioning
confidence: 97%
See 2 more Smart Citations
“…Compared to the original Update-Stress-First algorithm by Wallstedt and Guilkey (2008), a large gain in numerical stability and accuracy is obtained at the cost of slightly increased computational effort, for more details see Nairn (2003). In a first step, the new particle velocities are again interpolated to the grid nodes:…”
Section: Computation Of Velocity Gradientmentioning
confidence: 99%